Perception of Stress and Professional Burnout among Dental students during clinical years - Asadullah, Amna Nauman Khan, Aneela Amjad, Nauman Rauf Khan, Nighat Zahid, Nasrullah Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dentistry is associated with numerous stressors and dental students encounter a lot of stress during their undergraduate studies. This study was conducted with the objectives to know the understanding of stress and factors among the clinical dental students. Aim: To determine the perception of stress and professional burnout and determine the possible factors of it among dental students at College of Dentistry Sharif Medical and Dental College Lahore. Methodology: A cross sectional study was carried out in May 2021 on 3rd and final year BDS students from Sharif Medical and Dental College Lahore by using modified dental environmental stress questionnaire. SPSS vn 23.0 was used. Results: Male students are mostly affected by rules and regulations (36%) and lack of time to do schoolwork (36%) whereas female students are mostly affected by fear of failing exam (65%) whereas female students are mostly affected by fear of failing exam (65%). Whereas a highly significant association is seen between fear of failing exam and gender i.e.,<0.0001 for the major cause of causing stress. Conclusion: The result of this study shows that dental students of clinical years do suffer from stress. Syllabus and examination pattern should be amended to decrease stress as well as faculty attitude should be more supportive. Counselling sessions should be arranged for student’s better performance. Keywords: Stress, Burnout, Clinical dental students